(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
This paper explores the possible barriers that prevent micro-business owners (with a specific focus on the participants in the Self Employment Assistance Program in Cornwall Ontario Canada from outsourcing non-essential services. The paper will include both primary and secondary research to ascertain those barriers. The Findings show that although the respondents of the survey are aware of the benefits of outsourcing their non-essential business activities, they are still reluctant to outsource activities beyond the year-end tax preparation. It seems apparent that the respondents see outsourcing as an option for bigger businesses as 79.2% of them said they would outsource when their business grew.